Combination HIV Prevention: Significance, Challenges, and Opportunities - Kurth, Ann E. (2011)
No single HIV prevention strategy will be sufficient to control the HIV pandemic. However, a growing number of interventions have shown promise in partially protecting against HIV transmission and acquisition, including knowledge of HIV serostatus, behavioral risk reduction, condoms, male circumcision, needle exchange, treatment of curable sexually transmitted infections, and use of systemic and topical antiretroviral medications by both HIV-infected and uninfected persons. Designing the optimal package of interventions that matches the epidemiologic profile of a target population, delivering that package at the population level, and evaluating safety, acceptability, coverage, and effectiveness, all involve methodological challenges. Nonetheless, there is an unprecedented opportunity to develop “prevention packages” that combine various arrays of evidence-based strategies, tailored to the needs of diverse subgroups and targeted to achieve high coverage for a measurable reduction in population-level HIV transmission. HIV prevention strategies that combine partially effective interventions should be scaled up and evaluated.